A Novel Perturbative Iteration Algorithm for Effective and Efficient Solution of Frequency-Dependent Eigenvalue Problems (Advances in Applied Mathematics and Mechanics, 2012)
Many engineering structures exhibit frequency dependent characteristicsand analyses of these structures lead to frequency dependent eigenvalue problems.This paper presents a novel perturbative iteration (PI) algorithm which canbe used to effectively and efficiently solve frequency dependent eigenvalue problemsof general frequency dependent systems. Mathematical formulations of theproposed method are developed and based on these formulations, a computer algorithmis devised. Extensive numerical case examples are given to demonstratethe practicality of the proposed method. When all modes are included, the methodis exact and when only a subset of modes are used, very accurate results are obtained.